Factors that contribute the satisfactions among consumer towards the water supply in Merbok, Kedah / Nor Azira Sukarnor and Nurul Nabila Zainol - Sukarnor, Nor Azira; Zainol, Nurul Nabila (2018)
The objective of this research is to study the relationship between customer satisfaction and the factor that contribute which are availability of water, service provider and quality of water. A total respondent 375 people that lives in Merbok were selected to fill the set of questionnaire that consist of 5 sections which are Demographic Information (section A), Consumer Satisfaction (Section B), Availability of Water (Section C), Service Provider (Section D) and Quality of Water (Section E). The data was analyzed with Descriptive Statistics and Pearson Correlation of Statistical Package for Social Sciences (SPSS) version 2.0. The result indicates that there were positive correlations between consumer satisfactions and factor that influences which are availability of water, service provider and quality of water.